Peran Guru Dalam Memberikan Layanan Bimbingan Belajar Menulis Permulaan Pada Siswa Kelas 1 SD Muhammadiyah 23 Semanggi Surakarta - Pahlevi, Ardiansyah Widya; , Dra. Rismanawati, M.Pd (2017)
This study aims to describe (1) the implementation of preliminary learning guidance, (2) the role of teachers in carrying out initial writing tutorial, (3) obstacles and solutions of teachers in providing initial writing guidance on students of class 1 SD Muhammadiyah 23 Semanggi Surakarta. This research is a type of qualitative research and uses a single case study design study. Data collection techniques used interviews, obsevation, and documentation. Data analysis techniques with data reduction, data presentation, and data clarification. The validity of this research data with source triangulation and method triangulation. The results of this research are (1) the implementation of the initial writing guidance is the responsibility of the first grade teacher so that the grade 1 teacher is expected to guide and provide the material related to the improvement of writing skill ability, (2) the role of the teacher in carrying out the initial writing guidance is leter recognation , copying, fine or beautiful writing, name writing, and simple composing and use of the media in early writing lessons (3) teacher constraints in doing initial writing guidance are the lack of focus and attention of students, students engrossed in playing alone or with peers, Resulting in students experiencing delays in receiving writing materials. So the teacher's solution in dealing with these obstacles is with the teacher's own effort which is the responsibility of the teacher in the learning activity. One of the teacher's attempts to overcome the initial writing constraints is to provide additional hours for students who are late in writing, intensive and continuous learning guidance to develop writing skills.